2019
DOI: 10.1111/are.14298
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prebiotic potentials in selected leaf meals of high dietary fibre on growth performance, body composition, nutrient utilization and amylase activities of a tropical commercial carp fingerlings

Abstract: The performance of selected leaf meals of high dietary fibre in the feed of a tropical commercial carp, hybrid lemon fin barb (Barbonymus gonionotus ♀ × Hypsibarbus wetmorei ♂) was evaluated in a 56‐day feeding trial. The tropical carp juveniles (9.43 ± 0.05 g) were randomly stocked in 60‐L aquaria at 15 fish per aquarium. Five isonitrogenous and isocaloric diets (30% crude protein, 17 kJ/g gross energy) containing no leaf meal and 10% napier grass (Pennisetum purpureum), alfalfa (Medicago sativa), water spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 58 publications
(75 reference statements)
3
12
0
Order By: Relevance
“…Similar observation was made by Hassaan et al (2017). The reduction in lipid level with increasing inclusion level recorded in this study is in consonance with the observation of Zhou et al (2011). Jimoh et al (2019 reported similar trends of results when hybrid lemon fin barb (Barbonymus gonionotus ♀ × Hypsibarbus wetmorei ♂) was fed diets containing selected leaf meals of dietary high fibre.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar observation was made by Hassaan et al (2017). The reduction in lipid level with increasing inclusion level recorded in this study is in consonance with the observation of Zhou et al (2011). Jimoh et al (2019 reported similar trends of results when hybrid lemon fin barb (Barbonymus gonionotus ♀ × Hypsibarbus wetmorei ♂) was fed diets containing selected leaf meals of dietary high fibre.…”
Section: Discussionsupporting
confidence: 93%
“…Growth performance and nutrient utilization of fish was determined following the methods described in Jimoh et al, (2019) for weight gain, feed conversion ratio, (FCR), Survival (%), protein efficiency ratio (PER), specific growth rate (SGR %/ day), and, net protein utilization (NPU) responses was calculated as…”
Section: Diet Performance Evaluationmentioning
confidence: 99%
“…Growth performance of the fish was calculated as described by Jimoh, Kamarudin, Sulaiman, and Dauda () as follows:Specific growth rate,0.333333emSGR%·normald-1=Ln Final weight0.333333emnormalg-Ln Initial Weight0.333333emnormalgDuration of trial0.333333emnormald×100.Weight gain,0.333333emWG%·g=Final weight0.333333emnormalg-Initial weightnormalgInitial weightnormalg×100.Survival%=Initial stocking-Dead fishInitial stocking×100.Protein efficiency ratio, PER=Fish weight gain0.333333emnormalgTotal protein intake0.333333emnormalgFeed conversion ratio, FCR=Total feed consumption0.333333emnormalgFish weight gain0.333333emnormalgDaily feed intake, DFI%normald-1=100×Total feed intake0.333333emnormalgduration of the feeding period×…”
Section: Methodsmentioning
confidence: 99%
“…Growth performance of the fish was calculated as described by Jimoh, Kamarudin, Sulaiman, and Dauda (2019) as follows:…”
Section: Fish Performancementioning
confidence: 99%
“…Growth response and feed utilization indices were assessed as explained in Jimoh et al. (2019) as follows:Mean weight gain(g)=Final mean weight(g)Initial mean weight(g)Weight gainfalse(%false)=Final weight0.333333em(g)Initial weight0.333333em(g)Initial weight0.333333em(g)×100Specific growth ratefalse(%false/dayfalse)=][ln0.166667emfinal weightln0.166667eminitial weighttime of culture×100Daily Feeding Rate0.333333emfalse(%false/dayfalse)=Total feed fedInitial Weight+Final Weight/2×56×100Feed conversion ratio0.333333em=Total feed fed(g)Weight gain(g)Protein efficiency ratio0.333333em=Weight gain(g)Total protein fed(g)Protein ProductiveValue(\% )…”
Section: Methodsmentioning
confidence: 99%